Operational Risk Identification and Mitigation of the Chemical Production Process of PT. X Using Failure-Mode and Effect Analysis (FMEA) and Chemical Health Risk Assessment (CHRA) Methods - Dandy Ananda; Naning Aranti Wessiani (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2023)
PT. X is a German-based multinational chemical company that produces surfactant as one of its products. As a chemical processing company, the operational activities of the production process in PT. X poses risks that could happen at any time. This research is conducted to identify, analyze, and propose mitigation plan for the risks in one of the plants operated by PT. X. Interviews are conducted to identify the risks using Fishbone diagram as the framework and the Ishikawa method to categorize the causes. There are 86 risks that are identified consisting of 51 operational risks and 35 risks of chemical exposure. To be more thorough, the identified operational risks are assessed using the Failure-Mode and Effect Analysis (FMEA) and the chemical exposure risks are assessed using the Chemical Health Risk Assessment (CHRA). From the 206 risk causes, 31% are caused by Man, 28% are caused by Machine, 22% are caused by Material, 15% are caused by Method, and 5% are caused by the Environment. The FMEA produces Risk Priority Number (RPN) which led to risk prioritizing using the Pareto diagram and risk mapping, resulting in 24 risks being prioritized that consists of 15 medium-level risks and 9 low-level risks with no high-level risk present. The CHRA produces Risk Rating (RR) and Level of Risk that resulted in 77 low-level and 19 moderate-level risks for risk for inhalation exposure, and 9 moderate-level risks and 86 high-level risks for the exposure through dermal contact. It produces the decision of 17 inadequate control measures for chemical exposures. These assessments are further processed to devise the appropriate contingency plan, mitigation plan, and action plan.